Pb uptake, accumulation, and translocation in plants: Plant physiological, biochemical, and molecular response: A review - Shafeeq Ur Rahman; Anzhen Qin; Muhammad Zain; Zain Mushtaq; Faisal Mehmood; Luqman Riaz; Sadiq Naveed; Mohammad Javed Ansari; Mohd Saeed; Irfan Ahmad; Muhammad Shehzad (Heliyon, 2024)
Lead (Pb) is a highly toxic contaminant that is ubiquitously present in the ecosystem and poses severe environmental issues, including hazards to soil-plant systems. This review focuses on the uptake, accumulation, and translocation of Pb metallic ions and their toxicological effects on plant morpho-physiological and biochemical attributes. We highlight that the uptake of Pb metal is controlled by cation exchange capacity, pH, size of soil particles, root nature, and other physio-chemical limitations. Pb toxicity obstructs seed germination, root/shoot length, plant growth, and final crop-yield. Pb disrupts the nutrient uptake through roots, alters plasma membrane permeability, and disturbs chloroplast ultrastructure that triggers changes in respiration as well as transpiration activities, creates the reactive oxygen species (ROS), and activates some enzymatic and non-enzymatic antioxidants. Pb also impairs photosynthesis, disrupts water balance and mineral nutrients, changes hormonal status, and alters membrane structure and permeability. This review provides consolidated information concentrating on the current studies associated with Pb-induced oxidative stress and toxic conditions in various plants, highlighting the roles of different antioxidants in plants mitigating Pb-stress. Additionally, we discussed detoxification and tolerance responses in plants by regulating different gene expressions, protein, and glutathione metabolisms to resist Pb-induced phytotoxicity. Overall, various approaches to tackle Pb toxicity have been addressed; the phytoremediation techniques and biochar amendments are economical and eco-friendly remedies for improving Pb-contaminated soils.